Belawai: Ecological Heritage of Rajang-Belawai-Paloh delta - Azalea Kamellia, Abdullah; Belinda, Lip; Chan, Yee Zen; Cindy, Peter; Hafida, Bolhen; Jason, Hon; Nazriman, Wagiman; Zora, Chan (VWVF-Malaysia (Sarawak Office), 2019)
WWF-Malaysia in Sarawak, under its Freshwater Management & Water Security Programme focuses on reducing threats and promoting better protection and management of the freshwater ecosystems. In 2015, WWF-Malaysia conducted a rapid assessment in the Rajang-Belawai-Paloh delta and discovered its potential in high conservation values for lrrawaddy dolphins and other species. Since then, more surveys have been conducted on the presence of the lrrawaddy dolphins and the condition of their habitats in this delta. This booklet aims to highlight some of the significant survey findings; the importance of mangrove ecosystems to sustain the habitat for fishes and dolphins; and promote environmental stewardship for the protection of this Rajang-Belawai-Paloh delta's ecological heritage.